login
a(n) = Sum_{k=1..n} (-1)^(n+k)*A087322(n,k).
0

%I #18 Feb 15 2021 22:36:10

%S 3,6,23,50,131,294,687,1530,3419,7502,16391,35490,76467,163830,349535,

%T 742730,1572875,3320478,6990519,14680050,30758243,64312646,134217743,

%U 279620250,581610171,1207959534,2505397607,5189752130,10737418259,22190664342

%N a(n) = Sum_{k=1..n} (-1)^(n+k)*A087322(n,k).

%H <a href="/index/Rec#order_05">Index entries for linear recurrences with constant coefficients</a>, signature (3,1,-7,0,4).

%F a(n) = ((n + 1)*2^(n + 2) - 3 + (4*n + 1)*(-1)^(n + 1))/6.

%F G.f.: (4*x^3 - 2*x^2 + 3*x - 3)*x/((-1 + 2*x)^2*(-1 + x)*(1 + x)^2).

%Y Cf. A087322.

%K nonn,easy

%O 1,1

%A _Petros Hadjicostas_, Feb 15 2021